In Vitro Study of Multi-Therapeutic Properties of Thymus bovei Benth. Essential Oil and Its Main Component for Promoting Their Use in Clinical Practice - Hassan, Sherif T. S. (J Clin Med, 2018)
Thymus bovei Benth. (TB) is an important plant in the traditional medicine of the Mediterranean region. This study investigates the health-promoting properties of TB essential oil (TB-EO) for its possible use in clinical practice with regards to its cytotoxic, anti-herpes simplex virus type 2 (HSV-2), and antihypertensive (through inhibition of human angiotensin-converting enzyme; ACE) properties. The phytochemical profile of EO (99.9%) was analyzed by Gas Chromatography with Flame-Ionization Detection (GC-FID) and Gas Chromatography-Mass Spectrometry (GC-MS). In this study, all biological methods were performed at the level of in vitro studies. The results showed that TB-EO exerted remarked cytotoxic properties against human cervical carcinoma cells, colon cancer cells, and lung adenocarcinoma cells with the half-maximal inhibitory concentration (IC(50)) values of 7.22, 9.30, and 8.62 µg/mL, respectively, in comparison with that of standard anticancer drug cisplatin with IC(50) values of 4.24, 5.21, and 5.43 µg/mL, respectively. Fascinatingly, TB-EO showed very weak cytotoxicity on the healthy human fetal lung fibroblast cells with an IC(50) value of 118.34 µg/mL compared with that of cisplatin (IC(50) = 10.08 µg/mL). TB-EO, its main component geraniol, TB-EO combined with acyclovir (ACV) along with standard ACV, have displayed pronounced inhibitory properties against the replication of HSV-2 with the half-maximal effective concentration (EC(50)) values of 2.13, 1.92, 0.81 and 1.94 µg/mL, respectively, with corresponding selectivity indices (SI) 98.59, 109.38, 259.26 and 108.25, respectively. TB-EO and geraniol at a concentration of 15 µg/mL showed prominent inhibitory activities against ACE with % of inhibition 95.4% and 92.2%, respectively, compared with that of standard inhibitor captopril (99.8%; 15 µg/mL). Molecular docking studies were performed to unveil the mechanism of action of geraniol as well as structural parameters necessary for anti-HSV-2 activity (through the inhibition of HSV-2 protease) and ACE inhibition. This is the first report on the chemical composition of Egyptian TB-EO along with the above-mentioned biological activities. Our results may be considered as novel findings in the course of a search for new and active anticancer, anti-HSV-2 and antihypertensive agents, and expand the medicinal value of this plant and its phytochemicals in clinical practice.